Biological characteristics and pathogenicity comparison of Nocardia seriolae isolated from Micropterus salmoides and Channa argus - Zhang, Wei; Zhou, Kexin; Huang, Lei; Yang, Na; Lin, Lingyun; Chen, Lu; Yao, Jiayun; Dong, Mingxin; Shen, Jinyu; Pan, Xiaoyi (Frontiers in Veterinary Science, 2024)
Nocardia seriolae is the primary pathogen causing nocardiosis in various fish species, leads to significant economic losses in the aquaculture industry. In this study, 10 bacterial strains isolated from Micropterus salmoides and Channa argus infected with nocardiosis, were identified as N. seriolae by physiological and biochemical identification, as well as 16S rDNA sequencing. Moreover, the key virulence-related genes such as ESX-1, T7SS-2, T7SS-3, EspG1, sodC, sod2 and ESAT6 were all positive, and showing high homology among different strains. Pathogenicity testing revealed mortality rates ranging from 70 to 100%, accompanied by the presence of white nodules in the viscera of deceased fish. The drug sensitivity test demonstrated that LY21811, the most lethal strain, exhibited high sensitivity to nine types of antibiotics, including azithromycin, doxycycline, florfenicol and compound sulfamethoxazole, yet showed complete resistance to β-lactam antibiotics. Additionally, the tannic acid also demonstrated potent inhibitory effects against LY21811, with a minimum inhibitory concentration of 0.0625 mg/mL. These results showed that N. seriolae originated from M. salmoides and C. argus in Zhejiang Province were highly conserved, demonstrating a high homogeneity in genetic characteristics, pathogenicity and antimicrobial susceptibilities. These results provide a foundation for further research on the pathogenic characteristics and disease prevention of N. seriolae infections.